An investigation of the factor structure of a German version of the Eating Disorder Symptom Impact Scale (EDSIS) among parents of adolescents and young adults with anorexia nervosa. (January 2023) - Zeiler, Michael; Truttmann, Stefanie; Philipp, Julia; Kahlenberg, Leonie; Wittek, Tanja; Franta, Claudia; Schneider, Andrea; Imgart, Hartmut; Zanko, Annika; Karwautz, Andreas; Wagner, Gudrun
Abstract: The aim of this study was to explore the factor structure, scale characteristics and convergent validity of a German version of the Eating Disorder Symptom Impact Scale (EDSIS). A total of 335 parents of adolescents and young adults with anorexia nervosa in inpatient or outpatient treatment completed the 24-item German translation of the EDSIS and other measures of caregiving burden and psychological distress. We tested a 4 vs. 6-factor model of the EDSIS using confirmatory factor analyses. The 6-factor model treating items as ordinal variables showed the best fit to the data (CFI = 0.949, RMSEA = 0.064). Strong invariance of this model was shown between the sample of mothers and fathers. Internal consistencies of the EDSIS scales were in the acceptable-to-good range. Bottom effects were observed for the 'Binge-Purge-Impacts' subscale only. Mothers had significantly higher EDSIS scores compared to fathers. The EDSIS total score and most of the subscores showed substantial positive correlations with caregivers' psychological distress, level of depression, anxiety and expressed emotion as well as negative associations with the level of perceived caregiving skills. The German version of the EDSIS is a useful tool to assess caregiving burden in mothers and fathers of patients with anorexia nervosa. Highlights: First validation of a German version of the Eating Disorder Symptom Impact Scale A 6-factor structure is preferable over the original 4-factor structure. Strong invariance of the factor structure was shown between mothers and fathers. Mothers showed higher levels of burden compared to fathers. This is a useful tool measuring caregiving burden in parents of patients with anorexia nervosa.